The concept of distributed leadership in education: diversity and evolution of approaches - Mandragelia , V. (Scientific notes of the pedagogical department, 2021)
The purpose of the article is to analyze the theoretical and practical aspects, methodological approaches associated with the concept of distributed leadership (DL). This notion is very complex, contradictory, and there are many opinions regarding its essence, content, and genesis in the history of science, key components. Recent integrated educational innovations, the dynamic development of digital technologies, and the constraints associated with the pandemic call for a stronger teamwork of faculty and students and a rethinking of the overall concept of leadership. Leadership roles are many and varied, from facilitation, collaboration and influence, as well as carrying other aspects such as power and prestige. It should be added that the concept of "distributed leadership" is closely related to related concepts, such as “shared leadership” (SL), “collective leadership”, “collaborative leadership”, “co-leadership”, “emergent leadership”, ”dispersed’ leadership” and so on. Distributed leadership has many different aspects that are difficult to clearly define, but the vast majority of experts agree that This is the transfer of attention from the specifics of leadership styles, which are determined by the qualitative psychological and behavioral characteristics of formal and informal leaders, to a broader and systemic context, a distinctive feature of which is teamwork and collective creativity. The article analyzes different approaches to distributed leadership and emphasizes the need for its practical application in the field of education. DL has a huge impact on the qualitative improvement of the organizational culture of the team, the development of optimal solutions to complex problems, contributes to the preparation of proactive, creative individuals. This is very important in the field of education in a pandemic, when the role of digital technologies and the creativity of teachers is significantly increasing. It should also be emphasized that there is a close link between DL and the effectiveness of teachers.